Here's the solution, with correct order of operations:
$$
\begin{alignat}{2}
&\cssId{s19}{1 + 1 + 1 + 1 + 11 + 1 + 1 + 1 + 11 + 1\times 0 + 1}&& \cr
&\qquad\cssId{s20}{= 1 + 1 + 1 + 1 + 11 + 1 + 1 + 1 + 11 + (1\times 0) + 1} &\qquad&\cssId{s21}{\text{(the multiplication gets done first)}} \cr
&\qquad\cssId{s22}{= 1 + 1 + 1 + 1 + 11 + 1 + 1 + 1 + 11 + 0 + 1}\cr
&\qquad\cssId{s23}{= 30}
\end{alignat}
$$
If this doesn't make sense to you, try the following mental exercise on a shorter (but similar) problem:
$1 + 2 \times 0 + 3$
 Replace each plus sign with an (equallyweak) person.

Replace the multiplication sign with a strong person.
Why?
Multiplication is ‘stronger than’ addition!
And this makes perfectly good sense, since multiplication is ‘superaddition’:
for example, $\,5\times 2 = 2 + 2 + 2 + 2 + 2\,$.
 The first (leftmost) weak guy is trying to pull together the $\,1\,$ and the $\,2\,$, to add them.
 The middle (strong) guy is trying to pull together the $\,2\,$ and the $\,0\,$, to multiply them.
 The rightmost weak guy is trying to pull together the $\,0\,$ and the $\,3\,$, to add them.

Who wins?
Clearly, the strong guy!
1
2
0
3
$$
\cssId{s37}{1 + 2 \times 0 + 3}
\ \ \cssId{s38}{=\ \ 1 + \overbrace{(2\times 0)}^{\text{strong guy wins}} + 3}
\ \ \cssId{s39}{=\ \ 1 + 0 + 3}
\ \ \cssId{s40}{=\ \ 4}$$
MORE EXAMPLES:
$\cssId{s42}{1 + 3\times 5  2}
\cssId{s43}{= 1 + (3\times 5)  2}
\cssId{s44}{= 12}$
$\cssId{s45}{2  10\div 5 + 3}
\cssId{s46}{= 2  \frac{10}{5} + 3}
\cssId{s47}{= 3}$